408 A retrospective study of uterine smooth muscle tumor of uncertain malignant potential (uSTUMP): an analysis of 19 cases. (18th September 2019) - Gu, C; Chen, X; Ning, C
Abstract : Objectives: The present study aimed to evaluate the clinicopathologic features, prognosis and follow-up of uterine smooth muscle tumor of uncertain malignant potential (uSTUMP) in a single institution. In addition, we described the obstetric outcomes after uterine-preserving surgery for uSTUMP. Methods: A retrospective chart review was performed of patients diagnosed with uSTUMP between January 2001 and December 2015 in the Obstetrics and Gynecology Hospital, Fudan University. Variables of interest included the patients' demographics, morphological parameters, therapeutic results, time to recurrence, disease-free and overall survival, and subsequent obstetric outcomes. Pathology reviews were carried out by two pathologists (Z.L.H. and Z.C.Y.). Results: Nineteen patients with an initial diagnosis of uSTUMP were included in the study, and three of them were interpreted as sarcoma after slide review. In total, 16 patients with a final diagnosis of STUMP were available. The recurrence-free survival (RFS) curves differed significantly between uSTUMP and sarcoma group (p=0.003). One uSTUMP patient (6.3%) developed a recurrence as uSTUMP during the follow-up period. The clinical characteristics and histology features did not show significant correlations with recurrence, nor was the surgery type (uterus conserving versus hysterectomy) and surgery approach. Six uSTUMP patients requested uterine-preserving treatment, and two of whom wanted to become pregnant. Both of them (2/2) successfully delivered live birth without tumor recurrence. Conclusions: The patients of uSTUMP deserve a pathology review process in centers with experience. Recurrences can be rapid or slow in the form of uSTUMP or LMS. Fertility-preserve management is worth attempting in young patients with close follow-up.